2014
DOI: 10.1124/jpet.114.218131
|View full text |Cite
|
Sign up to set email alerts
|

M1 Polarization Bias and Subsequent Nonalcoholic Steatohepatitis Progression Is Attenuated by Nitric Oxide Donor DETA NONOate via Inhibition of CYP2E1-Induced Oxidative Stress in Obese Mice

Abstract: Activation of M1 macrophages in nonalcoholic steatohepatitis (NASH) is produced by several external or endogenous factors: inflammatory stimuli, oxidative stress, and cytokines are known. However, any direct role of oxidative stress in causing M1 polarization in NASH has been unclear. We hypothesized that CYP2E1-mediated oxidative stress causes M1 polarization in experimental NASH, and that nitric oxide (NO) donor administration inhibits CYP2E1-mediated inflammation with concomitant attenuation of M1 polarizat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 38 publications
1
30
0
Order By: Relevance
“…These findings support the hypothesis that an increased formation of reactive oxygen species -be it through endotoxin-dependent signaling cascades or other mechanisms -is critical in the development of NAFLD. It was further suggested that an endotoxin-dependent activation of Kupffer cells in the liver leads to an M1 polarization of these cells, which in turn further contributes to the onset and progression of inflammatory processes in the liver [18,46,47]. In the present study, elevated endotoxin and TLR-4 levels found in mice fed fructose, fat or a combination of both were associated with a reduced expression of Arg-1 and induction of MCP-1 in liver, suggesting that the development of NAFLD in these mice was associated with a change in polarization of Kupffer cells and infiltrating macrophages in liver.…”
Section: 1mentioning
confidence: 99%
“…These findings support the hypothesis that an increased formation of reactive oxygen species -be it through endotoxin-dependent signaling cascades or other mechanisms -is critical in the development of NAFLD. It was further suggested that an endotoxin-dependent activation of Kupffer cells in the liver leads to an M1 polarization of these cells, which in turn further contributes to the onset and progression of inflammatory processes in the liver [18,46,47]. In the present study, elevated endotoxin and TLR-4 levels found in mice fed fructose, fat or a combination of both were associated with a reduced expression of Arg-1 and induction of MCP-1 in liver, suggesting that the development of NAFLD in these mice was associated with a change in polarization of Kupffer cells and infiltrating macrophages in liver.…”
Section: 1mentioning
confidence: 99%
“…Simvastatin [3-hydroxy-3-methylglutaryl coenzyme A (HMG-CoA) reductase inhibitor], which is known to increase eNOS activity and thus NO production, was also shown to mitigate NASH-related liver fibrosis by inhibiting HSC activation [74]. NO donors also showed preventive roles in hepatic steatosis by facilitating fatty acid β-oxidation [75] and by blocking cytochrome P450 2E1 enzyme (CYP2E1)-mediated oxidative stress [76]. …”
Section: No and Liver Diseasesmentioning
confidence: 99%
“…As mentioned earlier, CYP2E1 has been reported to be markedly induced following HFD or under diabetes, and obesity whereas CYP2E1 -null mice have been protected, at least partially but significantly, from the CYP2E1-mediated deleterious effects of NAFLD [38, 110, 111, 120122]. In addition, over-expression of hepatic CYP2E1 both in vitro and in vivo promotes the development of hepatic insulin resistance, partly through the activation of c-Jun N-terminal protein kinase (JNK) [116, 123].…”
Section: Nafld and Cyp2e1mentioning
confidence: 99%